PELAKSANAAN FUNGSI PENGAWASAN DEWAN PERWAKILAN RAKYAT DAERAH (DPRD) TERHADAP PEMERINTAHAN DAERAH DIBIDANG ANGGARAN PEMBANGUNAN - GUSTANGKOT S (Journal Ilmu Sosial, Politik dan Pemerintahan, 2017)
Members of the Regional People's Legislative Assembly (DPRD) of Murung Raya Regency as an element of Local Government Organizer have three functions namely, the function of legislation, supervisory function and budget function. Duties and Powers Supervision possessed by the Regional People's Legislative Council of Murung Raya Regency is the authority granted by the Law in supporting the performance of DPRD in overseeing the Performance of Regional Government in implementing Development. The purpose of this study describes the Implementation of the Supervisory Function of the Regional People's Legislative Assembly (DPRD) against the Regional Government in the Development Budget (Studies in Murung Raya Regency). The research method used is data collection technique with descriptive qualitative approach and by way of observation, interview, and documentation. Based on the results of the research and findings in the field, the DPRD members perform the implementation and supervisory function in the development budget field in accordance with their duties and responsibilities and also the DPRD to cooperate with the Public Worker in supervising the development carried out in Saripoi Tanah Siang Selatan Village, Murung Raya Regency. In the implementation of their duties the members of the DPRD have supporting and inhibiting factors in the supervision of the development budget, DPRD Murung Raya is expected to further improve the implementation of the Supervision Function in the Regional Government Development Budget, especially in the District of Murung Raya.